ANALISIS DAMPAK EKONOMI EKOWISATA PULAU BERAS BASAH KOTA BONTANG (Economic Impact Analysis Of Beras Basah Island Ecotourism In Bontang City) - FADLI, FADLI; NIKHLANI, ANDI; ASIKIN, ANDI NOOR; JAILANI, JAILANI; FITRIYANA, FITRIYANA; ERWIANTONO, ERWIANTONO (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
Beras Basah Island in Bontang City has become one of the attractions of marine ecotourism.  Ecotourism activities on Beras Basah Island cause an economic impact on local communities. So this study aims to determine the economic impact of ecotourism on Beras Basah Island, Bontang City. The data analysis method used is a multiplier analysis consisting of Keynesian Local Multiplier Income, Ratio Income Multiplier Type I and Ratio Income Multiplier Type II. Based on the results of the analysis conducted, it can be concluded that the ecotourism business on Beras Basah Island has not had an impact on the local community, this can be seen in the Keynesian Income Multiplier of 0.22, the Type I Income Multiplier Ratio was recorded at 1.47 and the Type II Income Multiplier Ratio was 1.91.